The Highly Expressed FAM83F Protein in Papillary Thyroid Cancer Exerts a Pro-Oncogenic Role in Thyroid Follicular Cells - Fuziwara, Cesar Seigi; Saito, Kelly Cristina; Leoni, Suzana Garcia; Waitzberg, Ângela Flávia Logullo; Kimura, Edna Teruko (Frontiers in Endocrinology, 2019)
Thyroid cancer is the most common endocrine cancer with predominant prevalence of papillary thyroid cancer (PTC) histotype. MAPK signaling genetic alterations are frequent in PTC, affecting more than 80% of cases. These alterations constitutively activate MAPK signaling cross-regulating different pro-oncogenic pathways. However, additional molecular alterations associated with thyroid cancer are not completely understood. In this extent, the new family of proteins named FAM83 (FAMily with sequence similarity 83) was recently identified as mediator of oncogenic signaling in different types of cancer. Here we report FAM83F as a novel highly expressed protein in PTC. We evaluated FAM83F levels in 106 PTC specimens, 34 goiter, and 41 adjacent non-tumoral human thyroid, and observed FAM83F cytoplasmic overexpression in 71% of PTC (76 of 106) while goiter tissues showed nuclear positivity and normal thyroid showed no staining by immunohistochemistry. Moreover, TSH-induced goiter and BRAFT1799A-induced PTC animal models also showed FAM83F activation. In vitro, we generated a stable thyroid cell line PCCL3 with FAM83F overexpression and observed that FAM83F deregulates thyroid follicular cell biology leading to loss of thyroid differentiation genes such as Sodium-Iodide Symporter (NIS), reactivation of stem cell markers such as LIN28B and SOX2, induction of cell migration and resistance to doxorubicin-induced apoptosis. Moreover, FAM83F activates MAPK signaling through interaction with BRAF and RAF while impairs TGFβ antiproliferative signaling transduction. In this study, we showed FAM83F as a new pro-oncogenic protein overexpressed in thyroid cancer that modulates thyroid follicular cell biology and differentiation through cross-regulation of MAPK and TGFβ signaling.